Refleksi Fenomena Judicialization of Politics pada Politik Hukum Pembentukan Mahkamah Konstitusi dan Putusan Mahkamah Konstitusi - Indra Perwira (Jurnal Konstitusi, 2016)
This paper aims  to  introduce  the  phenomenon  of  judicialization  of  politics in the treasury of  legal  thought  in  Indonesia.  In  addition,  this  paper  also  aims to reflect the presence of judicialization of politics in the  Constitutional  Court, either through legal policy  on  establishment  of  constitutional  court  or  through its decisions. Theoretically, the phenomenon of judicialization of politics began to be known at the beginning of the 21st century characterized by the dependence of society to the court to resolve the issues related to morality, public policy, and political controversies. The presence of judicialization of politics can be reflected from the shift in the political settlement of the case which was originally made through political mechanisms to the settlement through a judicial mechanism. To see the phenomenon, this paper will explore the legal policy on establishment of the Constitutional Court. Through a historical perspective on the establishment, this paper would like to indicate that, in nature, the Constitutional Court is a political institution. In addition, this paper also analyzes the Constitutional Court decision in the case of judicial review on “Perpu” of the Corruption Eradication Commission (KPK) and the decision regarding the dispute Election East Java province in 2008,  to show that the phenomenon of judicialization of politics has lived and practiced  in the Constitutional Court as well.